2012
DOI: 10.1128/mcb.06663-11
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a Novel Androgen Receptor Target Gene, the Cyclin B1 Gene, through Androgen-Dependent E2F Family Member Switching

Abstract: The malignant transformation of human prostatic epithelium is associated with the loss of androgen receptor (AR) in the surrounding stroma. However, the function and mechanisms of AR signaling in prostate cancer (PCa) stroma remain elusive. Here we report, by using proteomics pathway array analysis (PPAA), that androgen and its receptor inhibit the proliferation of prostate stromal cells through transcriptional suppression of cyclin B1, and we confirmed our findings at mRNA and protein levels using AR-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 40 publications
(51 reference statements)
0
28
0
Order By: Relevance
“…More importantly, cyclin B1 expression level is affected dramatically by the phosphorylation level of Akt, which indicates that p-Akt might be involved in the transcription regulation of cyclin B1. AR has been shown in prostate cancer epithelial cells to influence the expression levels and activities of several cell-cycle genes essential for the G 1 -S and G 2 -M cell-cycle transition (40,47). In addition, Akt regulates the expression and stability of AR at multiple levels, ranging from transcriptional to posttranslational modulation (48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, cyclin B1 expression level is affected dramatically by the phosphorylation level of Akt, which indicates that p-Akt might be involved in the transcription regulation of cyclin B1. AR has been shown in prostate cancer epithelial cells to influence the expression levels and activities of several cell-cycle genes essential for the G 1 -S and G 2 -M cell-cycle transition (40,47). In addition, Akt regulates the expression and stability of AR at multiple levels, ranging from transcriptional to posttranslational modulation (48).…”
Section: Discussionmentioning
confidence: 99%
“…Li and colleagues found that transactivation of cyclin B1 in LNCaP cell was increased by androgen and AR (40). We assumed that AR transcription activity for cyclin B1 might be enhanced by overexpressed Jagged1 through Akt phosphorylation.…”
Section: P-akt Increases Cyclin B1 Expression By Enhancing Ar Recruitmentioning
confidence: 99%
See 1 more Smart Citation
“…A threshold model was proposed where genes that regulate cell proliferation or apoptosis are induced by different levels of E2F that act as positive or negative regulators of cell growth (53). Positive and negative cooperation in gene regulation by AR and E2F1 were reported in prostate cancer cells (95)(96)(97). Relative levels of MAGE-A11 and p107 influence AR and E2F1 transcriptional activation or repression.…”
Section: Primate-specific Transcriptional Coregulator Mage-a11-mentioning
confidence: 99%
“…In addition, the PLK1 and Cyclin B1 promoters are positively regulated by E2F family members2829. Therefore, we determined the effect of panobinostat treatment on the expression of E2F family members in synchronised cells (figure 7A).…”
Section: Resultsmentioning
confidence: 99%